2021
DOI: 10.3390/nu13124504
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and the Risk of Hyperuricemia: A Cross-Sectional Study in Chinese Adult Residents

Abstract: Background: Dietary Inflammatory Index (DII) scores have been consistently associated with several chronic diseases. This study explored the correlation between the DII and hyperuricemia in Chinese adult residents. Methods: The study included 7880 participants from the China Health and Nutrition Survey (CHNS), which was taken in in 2009. A 3-day 24 h meal review method was used to collect diet data and to calculate the DII score. Serum uric acid was obtained to determine hyperuricemia levels. Subjects were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Interestingly, some of these core targets were proinflammatory factors, such as TNF, IL6, and IL1B. Evidence has demonstrated that inflammation is significantly implicated in the pathogenesis of HUA [51][52][53]. Specifically, Nod-like receptor protein 3 (NLRP3) inflammasome is frequently activated during HUA, leading to the secretion of IL1B and other proinflammatory cytokines [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of these core targets were proinflammatory factors, such as TNF, IL6, and IL1B. Evidence has demonstrated that inflammation is significantly implicated in the pathogenesis of HUA [51][52][53]. Specifically, Nod-like receptor protein 3 (NLRP3) inflammasome is frequently activated during HUA, leading to the secretion of IL1B and other proinflammatory cytokines [52].…”
Section: Discussionmentioning
confidence: 99%
“…Hye et al suggested that higher proin ammatory dietary score was linked to the increased odds of hyperuricemia, but the association was only signi cant among females [30]. Chen et al found that this association was signi cant in the whole population including men and women [31]. Similarly, our results on the association of DII and hyperuricemia remained signi cant among men and women after subgroup analyses.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, myocardial infarction, heart failure, and elevated serum uric acid are associated with some common risk factors. For example, dyslipidemia, obesity, frequent consumption of fried foods, smoking, alcohol consumption [9][10][11][12][13][14]. Serum uric acid also interacts with multiple serum markers (creatinine, hemoglobin, platelets) as a dynamic oxidative stress indicator.…”
Section: Discussionmentioning
confidence: 99%